Components of cognitive–behavioural therapy for mitigating core symptoms in attention-deficit hyperactivity disorder: a systematic review and network meta-analysis - Sayo Hamatani; Kazuki Matsumoto; Yoshihiko Kunisato; Yoshifumi Mizuno (BMJ Mental Health)
Question Cognitive–behavioural therapy (CBT) is frequently implemented for individuals with attention-deficit hyperactivity disorder (ADHD). It is still unknown which specific components are effective, because CBT is a complex intervention with several components. The objective of this review was to assess the efficacy of CBT components for ADHD.Study selection and analysis Building on definitions of the components used in CBT strategies, we conducted network meta-analyses to evaluate the efficacy at both the treatment level (ie, combinations of these components) and the component level (ie, individual component). Primary outcome was treatment response of ADHD core symptoms. Secondary outcomes were total ADHD symptoms, inattention symptoms, hyperactivity-impulsivity symptoms and dropout from the treatment. We searched MEDLINE (via PubMed), Embase, PsycINFO, ClinicalTrials.gov and Cochrane Library for literature published up to 31 March 2022. This review included only randomised controlled trials.Findings 43 trials with 3817 participants were included in the network meta-analyses. Third-wave therapy (OR=4.80, 95% credible interval (CrI) 2.50 to 9.10), behaviour therapy (OR=3.50, 95% CrI 1.70 to 7.30) and CBT (OR=3.10, 95% CrI 1.70 to 5.70) were treatments that demonstrated superior efficacy compared with placebo. The component-level analyses showed organisational strategies (incremental OR (iOR)=2.03, 95% CI 1.27 to 3.24) and third-wave components (iOR=1.95, 95% CI 1.30 to 2.93) were associated with increase in treatment response. Problem-solving techniques (incremental standardised mean difference=0.42, 95% CI 0.01 to 0.83) were associated with a reduction in inattention symptoms.Conclusions Our findings suggest that the optimal treatment package for ADHD may include organisational strategies, third-wave components and problem-solving techniques.PROSPERO registration number CRD42022323898.